Reproduction misconceived: why there is no right to reproduce and the implications for ART access - Hall, Georgina Antonia (Journal of medical ethics, 2024)
Reproduction is broadly recognised as fundamental to human flourishing. The presumptive priority of reproductive freedom forms the predominant position in the literature, translating in the non-sexual reproductive realm as an almost inviolable right to access assisted reproductive technology (ART). This position largely condemns refusal or restriction of ART by clinicians or the state as discriminatory. In this paper, I critically analyse the moral rights individuals assert in reproductive pursuit to explore whether reproductive rights entitle hopeful parents to ART. I demonstrate that none of the protected actions performed, or entitlements generated are sui generis ‘reproductive’ rights, leading to the claim that there is no such thing as a right to reproduce. Under scrutiny, the reproductive right is a far narrower and weaker rights assertion than is recognised in the literature. I argue that the predominant position is grounded in a fundamental misunderstanding of the scope and strength of reproductive claims. I also highlight a significant conceptual inconsistency in the literature. On one hand, there is broad consensus that reproductive rights are predominantly negative, yet access to fertility treatment is framed as a component of the right. This wrongly contorts the negative nature of reproductive rights into a positive claim-right to ART. I conclude that this mistakenly frames ART access as sitting within the scope of reproductive freedom. I offer a revised conceptual paradigm of reproductive rights that has important clinical and policy implications for the provision and regulation of ART.